Relationship of floral morphology and development with the pattern of bee visitation in a species with pollen-flowers, Chamaecrista desvauxii (Fabaceae) - Nogueira, Anselmo; Valadão-Mendes, Lorena B. [UNESP]; El Ottra, Juliana H.L.; Guimarães, Elza [UNESP]; Cardoso-Gustavson, Poliana; Quinalha, Marília Monteiro [UNESP]; Paulino, Juliana Villela; Rando, Juliana Gastaldello (Oxford University Press (OUP), 2018)
Chamaecrista exhibits a suite of floral traits associated with buzz pollination, and its morphology and organogenesis play crucial roles in pollination because bees can exploit anthers at distinct developmental stages. Here we investigated the relationship of floral morphology and development with the bee visitation pattern in Chamaecrista desvauxii var. latistipula. We also explored pollen structure, germination and stigma receptivity. Sepal growth was initially rapid and gradually slowed down as growth of the inner whorls accelerated. Heteranthery arose early during flower development and was not accompanied by morphological or histochemical differences in pollen grains, suggesting that stamen differentiation in the context of the 'division-of-labour' hypothesis was in no way associated with pollen differences. The stigma was receptive and pollen grains from both anther morphs were viable before anthesis. Bee species showed specific behaviours on anthers at both flower stages, from chewing to buzzing, in some cases touching the stigmatic region during pollen collection. Pollination experiments indicated similar fruit set between anthetic flowers and pre-anthetic buds, suggesting that pollination could occur before anthesis, even though floral buds have distinct whorl arrangements. This study highlights the existence of an extended window of opportunity for mutualistic interactions between bees and flowers in a typical species of Fabaceae with pollen-flowers.
Keywords: Brazil; Flower development; Leguminosae; Pollen grains; Pollination ecology; Pollinator behaviour